Given:
5 + 3(-2x + 1) = 16
Let's solve for x.
• Step 1:
Use distributive property to expand the parenthesis
5 + 3(-2x) + 3(1) = 16
5 - 6x + 3 = 16
• Step 2:
Combine like terms
-6x + 3 + 5 = 16
-6x + 8 = 16
• Step 3:
Subtract 8 from both sides
-6x + 8 - 8 = 16 - 8
-6x = 8
• Step 4:
Divide both sides by -6
![\begin{gathered} (-6x)/(-6)=(8)/(-6) \\ \\ x=-(4)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/w8wi8r8q1ke7qmtuwbux7kw3qj5rx4k0gq.png)
ANSWER:
![-(4)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/zz8fzloaagihdqz8rvvuss23nvw76ve065.png)
•